SPATIAL DISTRIBUTION OF SOME MICROELEMENTS IN SOIL IN THE AL-RIFAI DISTRICT OF THE DHI QAR GOVERNORATE - R. T. Al-Badiri; A. R. Jubier; M. S. Oleiwi (مجلة الأنبار للعلوم الزراعية)
This study was conducted in the Al-Rifai District, north of Dhi Qar Governorate in the southern region of Iraq (longitudes 46°11'10.21" to 46°21'45.98" east and latitudes 31°44'38.835" to 31°46'9.889" north). Thirty auger hole sites were identified to a depth of 0-30 cm and the coordinates of ten pedons determined using a GPS device. The horizons of the pedons were described in a basic morphological manner, and samples were collected from each site for laboratory analyses. The maps were produced in the Arc GIS 10.4 program according to the inverse distance weight method, and maps of the spatial distribution of the available microelements of Fe, Zn, and Cu were drawn. The results indicated that the highest content of iron available in the soil of the study area was at the Ap horizon of pedon 1 and the lowest content was at the C3 horizon of pedon 9. The highest content of available zinc in the study area was at site 24, while the lowest was at horizon C3 of pedon 10. For copper, the highest content was at site 20, while the lowest was at horizon C3 of pedon 10.